Composition of the fecal, vaginal and colostrum microbiotas of dams at parturition and their relationship with neonatal outcomes in dogs - Quentin Garrigues; Emmanuelle Apper; Fanny Mercier; Ana Rodiles; Nicoletta Rovere; Sylvie Chastant; Hanna Mila (Animal Microbiome)
Abstract Background Microbial seeding in early life is critical for the host’s short- and long-term health, and the mother is the first source of bacteria for the newborn. The objective of this study was to characterize the maternal fecal, vaginal, and colostral microbiotas in the canine species one day after parturition and to evaluate the relationship between the microbial profiles of 36 dams and the neonatal outcomes of 284 newborns. Results The first part of the study revealed the presence of 2 fecal, 3 vaginal, and 2 colostral microbial clusters on the basis of the core microbiota of the dams. Among these three maternal microbiotas, only the vaginal microbiome was found to be associated with neonatal outcomes. Compared with those in the other clusters, females in Cluster 1, with the lowest stillbirth and neonatal mortality ratios, presented a greater abundance of Moraxellaceae in their vaginal microbiota; Cluster 2, with a greater abundance of Pasteurellaceae, mostly from the Haemophilus genus; and Cluster 3 (with the highest stillbirth and neonatal mortality ratios), a greater abundance of Enterobacteriaceae, mostly E. coli. Moreover, Cluster 3 dams presented significantly lower species richness according to the Shannon index than did dams from the other clusters. Conclusions This study underscores the strong association between maternal microbiota, particularly the vaginal microbiota, and newborn health. The results of this study call for further research to gain a deeper understanding of the optimal vaginal microbiota composition in canine species and the ways to modulate it to improve neonatal outcomes.